Pengaruh Strategi Promosi Di Sosial Media Dan E-Word Of Mouth Marketing Terhadap Keputusan Pembelian: Studi Pada Konsumen Produk Luxcrime Di Kota Makassar - Nurfadillah Anton; Chalid Imran Musa; Muhammad Ilham Wardhana Haeruddin; Abdi Akbar Idris; Muhammad Ichwan Musa (EBISMAN eBisnis Manajemen, 2024)
This research aims to determine the impact of social media promotion strategy and e-word of mouth marketing on Luxcrime purchase decisions in Makassar City. The study adopts a quantitative approach with a descriptive design. The sample consists of 100 Luxcrime product consumers in Makassar City. Data collection is conducted through documentation and survey methods using questionnaires. Data analysis employs Partial Least Square (PLS) analysis. The research findings indicate that: social media promotion strategy positively influences Luxcrime product purchase decisions in Makassar City; social media promotion strategy positively influences e-word of mouth marketing for Luxcrime products in Makassar City; e-word of mouth marketing positively influences Luxcrime product purchase decisions in Makassar City; social media promotion strategy and e-word of mouth marketing simultaneously have a positive impact on Luxcrime product purchase decisions in Makassar City.